Perbedaan Hasil Pemeriksaan Jumlah Eritrosit Darah Vena Dengan Pembendungan Selama 50 Detik dan 80 Detik - Putri Lenda (Jurnal Laboratorium Prima, 2023)
Background : Torniquet containment is one that can affect the results of the erythrocyte count. Dam according to CLSI should not be more than 1 minute. But sometimes in taking venous blood there is damming for more than one minute. In this study, researchers examined the differences in the number of venous blood erythrocytes by damming for 50 seconds and 80 seconds. The results of this study found that there were differences in the number of erythrocytes with 50 seconds and 80 seconds of containment. Objective : Knowing the difference in the results of venous blood erythrocyte counts with damming for 50 seconds and 80 seconds. Methods : This research is a pre-experimental study with a cross-sectional approach using total sampling technique. The subjects of this study were 32 students who met the inclusion and exclusion criteria. Venous blood that has been collected by damming for 50 seconds and 80 seconds, then examined the number of erythrocytes using the Sysmex XP-100. Data from sample measurements were then tested using the Paired Sample t-test. Result : The average number of venous blood erythrocytes with damming for 50 seconds was 4.48x106/µl. The average number of venous blood erythrocytes with damming for 80 seconds was 4.50x106/µl. Conclusion : There is a difference in the results of examining the number of venous blood erythrocytes by holding 50 seconds and 80 seconds using the Sysmex XP-100 with a value (sig 2 tailed) 0,03> 0,05. Suggestion : Torniquet containment for 80 seconds cannot be used to check the RBC count.